Kecerdasan Emosional, Dukungan Sosial dan Kecenderungan Burnout - Robiatul Adawiyah, Raden Adjeng (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. This research aimed to find the relationships of emotional intelligence, social support and teachersâ€™ tendency to burnout. Subjects of the study were teachers of SMAN 3 Bangkalan. Data were collected by scales of emotional intelligence, social support and tendency to burnout, and then analyzed by statistical regression and partial correlation. ResultsÂ showed relationships significantly between emotional intelligence, social support and tendency to burnout. There was a negative correlation between emotional intelligence and tendency to burnout. There was a negative correlation between social support and tendency to burnout.Keywords: emotional intelligence, social support, burnoutÂ